Risk of prostate cancer and death after benign transurethral resection of the prostate—A 20‐year population‐based analysis. Issue 20 (17th August 2022) - Hilscher, Maria; Røder, Andreas; Helgstrand, J. Thomas; Klemann, Nina; Brasso, Klaus; Vickers, Andrew Julian; Stroomberg, Hein Vincent
Abstract : Background: The oncological risks after benign histology on a transurethral resection of the prostate (TURP) remain largely unknown. Here, the risk of prostate cancer incidence and mortality following a benign histological assessment of TURP is investigated in a population‐based setting. Methods: Between 1995 and 2016, 64, 059 men in Denmark underwent TURP without prior biopsy of the prostate; 42, 558 of these men had benign histology. The risks of prostate cancer, prostate cancer with a Gleason score ≥ 3 + 4, and prostate cancer–specific death were assessed with competing risks. Specific risks for pre‐TURP prostate‐specific antigen (PSA) levels at 10 and 15 years were visualized by locally estimated scatterplot smoothing. Results: The median age at TURP was 72 years (interquartile range [IQR], 65–78 years), and the median follow‐up was 15 years (IQR, 10–19 years). The 10‐year risks of any prostate cancer and prostate cancer with a Gleason score ≥ 3 + 4 and the 15‐year risk of prostate cancer death showed clear visual relations with increasing PSA. The 15‐year cumulative incidence of prostate cancer–specific death after benign TURP was 1.4% (95% confidence interval [CI], 1.3%–1.6%) for all men and 0.8% (95% CI, 0.6%–1.1%) for men with PSA levels <10 ng/ml. The primary limitation was exclusion due to missing PSA data. Conclusions: Men with low PSA levels and a benign TURP can be reassured about their cancer risk and do not need to be monitored differently than any other men. Patients with high PSA levels can be considered for further follow‐up with prostate magnetic resonance imaging. These findings add to the literature suggesting that normal histology from the prostate entails a low risk of death from the disease. Lay summary: There is little knowledge about the oncological risks after the surgical treatment of benign prostatic hyperplasia. This study shows a very low risk of adverse oncological outcomes in men with prostate‐specific antigen (PSA) levels below 10 ng/ml at the time of transurethral resection of the prostate. Patients with higher PSA levels may need more extensive follow‐up. Abstract : Men with low prostate‐specific antigen (PSA) levels and a benign transurethral resection of the prostate can be reassured about their cancer risk and do not need to be monitored differently than any other men, but patients with high PSA levels should be considered for further follow‐up. This study's findings add to a body of literature suggesting that normal histology from the prostate entails a low risk of death from the disease.